Optical total reflection and transmission with mode control in a dielectric subwavelength nanorod chain - 李浩 李伟 杜俊杰 武爱民 仇超 盛振 王曦 邹世昌 甘甫烷 (Chinese physics B, 2013)
We report a polarization dependent reflection phenomenon beyond the normal incidence witn a subwavelengm nanorod chain. Light waves of the transverse electric mode will be totally reflected while those of the transverse magnetic mode will transmit through. The total reflection or transmission phenomenon can be seen as a constructive or destructive interference of the incident field with the transverse mode field of the chain. With the low-loss feature and the ultra-compact characteristic, this structure may find applications in photonic circuits.